Privacy Preservation for Association Rule Mining - Jyothi, N. S. Mrudula; Kumar, A. Suraj (International Journal of Computer Sciences and Engineering, 2018)
Data mining is the process of extracting hidden patterns of data. Association rule mining is an important data mining task that finds an interesting association among a large set of a data item. Association rule hiding is one of the techniques of privacy-preserving data mining to protect the association rules generated by association rule mining. In this paper, proposed a new data distortion technique for hiding sensitive association rules. Algorithms based on this technique either hide a specific rule using data alteration technique or hide the rules depending on the sensitivity of the items to be hidden. The proposed technique uses the idea of representative rules to prune the rules first and then hides the sensitive rules.